2010
DOI: 10.1016/j.ijfatigue.2009.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue of biomaterials: Hard tissues

Abstract: The fatigue and fracture behavior of hard tissues are topics of considerable interest today. This special group of organic materials comprises the highly mineralized and load-bearing tissues of the human body, and includes bone, cementum, dentin and enamel. An understanding of their fatigue behavior and the influence of loading conditions and physiological factors (e.g. aging and disease) on the mechanisms of degradation are essential for achieving lifelong health. But there is much more to this topic than the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 102 publications
1
46
0
Order By: Relevance
“…Due to this architecture, its mechanical properties are generally reported as a function of density [329]. For cortical bone, alignment of the osteons with the bone's long axis bestows unique and beneficial anisotropy.…”
Section: Fracture Toughnessmentioning
confidence: 99%
“…Due to this architecture, its mechanical properties are generally reported as a function of density [329]. For cortical bone, alignment of the osteons with the bone's long axis bestows unique and beneficial anisotropy.…”
Section: Fracture Toughnessmentioning
confidence: 99%
“…Both the stress-life behavior and fatigue crack growth resistance of enamel and dentin have been studied. Detailed reviews of the fatigue behavior of hard tissues of the human body have been reported [108,128]. Thus, this portion of the review is focused on new results and only highlights previous findings.…”
Section: Evaluations On the Fatigue Properties Of Tooth Tissuesmentioning
confidence: 99%
“…Of note, previous studies were limited to quasi-static loading of the tissue to failure. Dentin is susceptible to degradation by fatigue (Arola et al, 2010), and small flaws may propagate by fatigue crack growth (Arola et al, 1999;Nalla et al, 2003). No study has examined whether the methods of cavity preparation are important to the fatigue behavior of coronal dentin.…”
Section: Introduction Tmentioning
confidence: 99%